Mechanistic insights on Ru nanoparticle in situ formation during hydrodeoxygenation of lignin-derived substances to hydrocarbons. Issue 5 (7th February 2023) - Naranov, Evgeny R.; Sadovnikov, Alexey A.; Arapova, Olga V.; Bugaev, Aram L.; Usoltsev, Oleg A.; Gorbunov, Dmitry N.; Russo, Vincenzo; Murzin, Dmitry Yu.; Maximov, Anton L.
Abstract : We present the quantitative conversion of guaiacol and diphenyl ether to cyclohexane over supported RuO2 catalyst. In situ reduction of the RuO2 species occurs simultaneously with the hydrogenation process, contributing to higher catalytic activity. Abstract : We present the conversion of guaiacol and diphenyl ether (DPhE) with ∼100% selectivity towards hydrocarbons over a ruthenium oxide-containing catalyst on a micro–mesoporous support (ZM). To elucidate the structure–catalytic activity correlation of the ruthenium oxide catalysts and achieve a high hydrocarbon yield via deoxygenation–hydrogenation, three supports were used: non-acidic mesoporous SBA-15, bulk ZSM-5 (CBV 3024E) and micro–mesoporous ZM. It was demonstrated that the acidity of the support was a key factor in the deoxygenation of guaiacol and DPhE, while a developed catalyst surface played an important role in the case of bulk molecule hydrogenation. The best catalytic performance was obtained over the micro–mesoporous RuO2 /ZM catalyst. Complete conversion of guaiacol and DPhE with a high cyclohexane yield of ∼100% was achieved after 1 h at 473–498 K under an initial H2 pressure of 50 bar in n -alkane solution. Operando XAS and in situ DRIFT spectroscopy analyses of the RuO2 -based catalysts during guaiacol hydrogenation revealed that the reaction initiates simultaneously with the formation of the metallic Ru phase. It was shown that RuO2 catalysts demonstrated better catalytic activity compared to reduced catalysts.